Molecular identification of whole squids and calamari at fairs and markets in regions of Latin America - Bianca Lima Paiva; Alan Erik Souza Rodrigues; Igor Oliveira de Freitas Almeida; Kamila de Fatima Silva; Manuel Haimovici; Unai Markaida; Patricia Charvet; Vicente Vieira Faria; Bruno B. Batista; Acácio Ribeiro Gomes Tomás; Luis Fernando da Silva Rodrigues-Filho; Jonathan Stuart Ready; et al. (Scientific Reports)
Abstract The commercial importance of cephalopods has increased considerably, being an important fishing resource. However, during the preparation for commercialization of those species, they suffer the process known as “finning” which includes removing and separating the head, arm, skin or even having the body structure cut into rings, which ends up making it difficult or often prevents the identification of the species, which can lead to replacements. In this sense, the present study aimed to use the large ribosomal region, rrnL (16S rDNA) to genetically identify cephalopod species sold in markets and fairs in Latin America. Whole and processed samples were collected from supermarkets and directly from local fishers the approximate collection location. Each generated sequence was submitted to the blastn portal for molecular comparison and included in the database for subsequent genetic identification. Our results indicate labeling errors in samples from the State of Pará that contained the species Dosidicus gigas found only in the Pacific Ocean and were generically labeled as “National Lula”. No type of substitution was found among the samples that were being sold at fairs and markets, only labeling errors. Thus, our results demonstrate the effectiveness of the rrnL for identifying species and evaluating labeling errors.